The emergent role of mind-mapping in CLIL instruction: textual cognitive resources in engineering lectures - Sancho Guinda, Carmen (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2010)
Starting out from the notion of irradiating thought or conceptual maps (Buzan 1986, 2002), recently and explicitly tackled as an academic skill by some CLIL learner-oriented materials, this article explores the prospects for its introduction in engineering environments. It reports on a small-case study aimed to reflect on the implications of lecturers' textual choices for the note-taking habits of engineering students and ultimately for their representation of contents. The analysis of seven engineering lectures in English and Spanish in a summer seminar for EU polytechnic students, of seven condensed lectures in English by engineering teachers during an in-service training course at the Universidad Politécnica de Madrid and of twenty questionnaires probing into the students' note-taking routines, suggests an influence of lecturing style on note quality and evidences several lecturing deficiencies at the rhetorical level that may hamper the practice of conceptual mapping.